A qualitative study of partnership between woman and midwife within midwife-led care clinic - Rizky Vaira; Yanti Yanti; Asri Hidayat (Universitas Aisyiyah Yogyakarta, 2020)
One indirect causes of maternal mortality in Indonesia is